The transfer of avoidance evoking functions through stimulus equivalence classes - Augustson, Erik M.; Dougher, Michael J. (Journal of behavior therapy and experimental psychiatry, 1997)
Recent research in the area of stimulus equivalence suggests that transfer of function via members of stimulus equivalence classes may have relevance to human emotional responding and the development and generalization of certain psychological disorders. This study investigated the transfer of avoidance evoking functions through equivalence classes. Eight subjects were trained in the necessary relations for two-four member stimulus equivalence classes to emerge. Next, using an on-baseline classical conditioning procedure, one member of one class was paired with shock while one member of the other class was presented without shock. Then, while subjects engaged a key-press task, a differential, signalled avoidance task was introduced wherein shock was avoided if a response occurred to the stimulus previously associated with shock. The remaining stimuli from both classes were then presented. The behavior of all eight subjects showed the differential transfer of the avoidance evoking function. The clinical and theoretical implications of the results are discussed.